On Some New Classes of $\mathcal{I}-$Convergent Sequences in GNLS - Vakeel Khan; Zahid Rahman; Ayhan Esi; Amit Kumar (Sahand Communications in Mathematical Analysis)
This paper is devoted to study $\mathcal{I}$-convergent,$\mathcal{I-}$null, $\mathcal{I-}$bounded and bounded sequence spaces in gradual normed linear spaces, denoted by $c_{\| · \|_G} ^\mathcal{I} ,c_{0 \| · \|_G} ^\mathcal{I} ,\ell_{∞ \| · \|_G} ^\mathcal{I}, \ell_{∞ \| ·\|_G}, m_{\| · \|_G} ^\mathcal{I}$ and $m_{0 \| · \|_G} ^\mathcal{I}$ respectively. We discussed some algebraic and topological properties of these classes. Also, we studied some inclusions involving these spaces.